CORROSION OF METALS AND METHODS OF PRESERVATION (Web of Teachers: Inderscience Research, 2024)
Corrosion is a natural process that transforms a refined metal into a chemically stable oxide. This is the gradual deterioration of materials (usually metal) as a result of a chemical or electrochemical reaction with the environment. Corrosion engineering is a field devoted to corrosion control and prevention.